Carbon sink strength of a Mediterranean cork oak understorey: how do semi-deciduous and evergreen shrubs face summer drought? - Correia, A. C.; Costa e Silva, F.; Correia, A. V.; Hussain, M. Z.; Rodrigues, A. D.; David, J. S.; Pereira, J. S. (Journal of Vegetation Science, 2013)
Questions How do semi-deciduous and evergreen shrubs exploit environmental resources during summer drought? What is the contribution of the understorey shrubby layer to ecosystem carbon assimilation? To what extent are carbon balance and transpiration impacted by a rain pulse? Location Cork oak open woodland in the Mediterranean region. Methods We used closed dynamic light and dark chambers to measure gas exchange (CO2 and H2O) in the dominant shrub understorey species Cistus salviifolius, Cistus crispus (semi-deciduous) and Ulex airensis (evergreen), together with plant physiological and morphological measurements during summer drought and autumn recovery. A hyperbolic light response model constrained by vapour pressure deficits was fitted for up-scaling shrub photosynthesis to the ecosystem level. The data were compared, on a daily and daytime basis, with gross primary productivity estimates from ecosystem eddy-covariance flux measurements. Results The onset of summer drought led to a significant leaf area reduction in semi-deciduous species. A general decrease in photosynthesis in all species was observed, while evapotranspiration and above-ground respiration fluxes contrasted among species during summer progression and autumn recovery. The shallow-rooted C. salviifolius was able to use light more efficiently than the other two species, although with poor stomatal control over water loss and consistently higher above-ground respiration rates, leading to lower water and carbon use efficiencies when compared with C. crispus. The deep-rooted shrub U. airensis maintained higher leaf water potentials and very low photosynthetic rates while decreasing transpiration rates throughout the summer drought. A summer rain pulse showed that shallow-rooted shrubs use water in an opportunistic way, with immediate leaf rehydration and concomitant photosynthesis increments. Conversely, deep-rooted shrubs (U. airensis) were unresponsive, only recovering photosynthesis with high soil water content. An opportunistic growth response may be disadvantageous to shallow-rooted shrubs in a future climate with extended dry summers and higher probability of rain pulse events. The prominent increase in transpiration rates and plant respiration costs observed during the dry conditions that followed the rain pulse, led to a reduced plant ability to recover after autumn rains. Conclusions The shrubs that naturaly colonized this montado understorey showed contrasting strategies to overcome summer drought, suggesting an efficient mosaic exploitation of seasonal environmental resources. The contribution of these shrubs to total ecosystem CO2 uptake during summer and autumn recovery was 17%. This high contribution implies that shrub density management decisions should consider a carbon balance perspective.
Keywords: Cistus sp; CO2; Eddy-covariance; H2O; Mediterranean; partitioning; Shrubs; Ulex sp; up-scaling

Modelling interception loss from evergreen oak Mediterranean savannas: Application of a tree-based modelling approach - Pereira, F. L.; Gash, J. H. C.; David, J. S.; David, T. S.; Monteiro, P. R.; Valente, F. (Agricultural and Forest Meteorology, 2009)
In a previous study, it was shown that an isolated, fully saturated tree-crown behaves like a wet bulb, allowing evaporation of intercepted rainfall to be estimated by a simple diffusion equation for water vapour. This observation was taken as the basis for a new approach in modelling interception loss from savanna-type woodland, whereby the ecosystem evaporation is derived by scaling up the evaporation from individual trees, rather than by considering a homogeneous forest cover. Interception loss from isolated trees was estimated by combining the aforementioned equation for water vapour ﬂux with Gash’s analytical model. A new methodology, which avoids the subjectivity inherent in the Leyton method, was used for estimating the crown storage capacity. Modelling performance was evaluated against data from two Mediterranean savanna-type oak woodlands (montados) in southern Portugal. Interception loss estimates were in good agreement with observations in both sites. The proposed modelling approach is physically based, requires only a limited amount of data and should be suitable for the modelling of interception loss in isolated trees and savannatype ecosystems
Keywords: Gash analytical model; Isolated trees; Quercus ilex; rainfall interception; Savannas; Wet bulb temperature

Water-use strategies in two co-occurring Mediterranean evergreen oaks: surviving the summer drought - David, T. S.; Henriques, M. O.; Kurz-Besson, C.; Nunes, J.; Valente, F.; Vaz, M.; Pereira, J. S.; Siegwolf, R.; Chaves, M. M.; Gazarini, L. C.; David, J. S. (Tree Physiology, 2007)
In the Mediterranean evergreen oak woodlands of southern Portugal, the main tree species are Quercus ilex ssp. rotundifolia Lam. (holm oak) and Quercus suber L. (cork oak). We studied a savannah-type woodland where these species coexist, with the aim of better understanding the mechanisms of tree adaptation to seasonal drought. In both species, seasonal variations in transpiration and predawn leaf water potential showed a maximum in spring followed by a decline through the rainless summer and a recovery with autumn rainfall. Although the observed decrease in predawn leaf water potential in summer indicates soil water depletion, trees maintained transpiration rates above 0.7 mm day−1 during the summer drought. By that time, more than 70% of the transpired water was being taken from groundwater sources. The daily fluctuations in soil water content suggest that some root uptake of groundwater was mediated through the upper soil layers by hydraulic lift. During the dry season, Q. ilex maintained higher predawn leaf water potentials, canopy conductances and transpiration rates than Q. suber. The higher water status of Q. ilex was likely associated with their deeper root systems compared with Q. suber. Whole-tree hydraulic conductance and minimum midday leaf water potential were lower in Q. ilex, indicating that Q. ilex was more tolerant to drought than Q. suber. Overall, Q. ilex seemed to have more effective drought avoidance and drought tolerance mechanisms than Q. suber.
10.1093/treephys/27.6.79310.1093/treephys/27.6.793
Keywords: canopy conductance; groundwater; Hydraulic conductance; leaf water potential; Quercus ilex; Quercus suber; sap flow

Rainfall interception by an isolated evergreen oak tree in a Mediterranean savannah - David, T. S.; Gash, J. H. C.; Valente, F.; Pereira, J. S.; Ferreira, M. I.; David, J. S. (Hydrological Processes, 2006)
Redistribution of ground-level rainfall and interception loss by an isolated Quercus ilex tree were measured over 2 years in a Mediterranean oak savannah. Stemﬂow, meteorological variables and sap ﬂow were also monitored. Rainfall at ground level was measured by a set of rain-gauges located in a radial layout centred on the tree trunk and extending beyond the crown limits. Interception loss was computed as the difference between the volume of rainwater that would reach the ground in the absence of the tree and the volume of water that actually fell on the ground sampling area (stemﬂow included). This procedure provided correct interception loss estimates, irrespective of rainfall inclination. Results have shown a clear non-random spatial distribution of ground-level rainfall, with rainwater concentrations upwind beneath the crown and rain-shadows downwind. Interception loss amounted to 22% of gross rainfall, per unit of crown-projected area. Stand interception loss, per unit of ground area, was only 8% of gross rainfall and 28% of tree evapotranspiration. These values reﬂect the low crown cover fraction of the stand (0Ð39) and the speciﬁc features of the Mediterranean rainfall regime (predominantly with few large storms). Nevertheless, it still is an important component of the water balance of these Mediterranean ecosystems
Keywords: interception loss; Isolated trees; Quercus ilex; rainfall interception; rainfall redistribution